2016
DOI: 10.1039/c5cc07605f
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and characterization of a benzylguanine-binding RNA aptamer

Abstract: Repurposing the “protein-labeling toolkit” for RNA research could be a pragmatic approach for developing new RNA-labeling methods. We have evolved an RNA aptamer that tightly binds benzylguanine (bG), the key ligand for the protein SNAP-tag. The aptamer tightly binds bG fluorophores and can be purified from cellular RNA with bG agarose under native conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…A different approach to producing a light-up aptamer is to bind and sequester a contact quencher covalently fused to a fluorophore, enabling easy switching of spectral properties by switching the fluorophore (Arora et al ., 2015). Finally, there is an aptamer that binds benzylguanine derivatives, enabling the use of SNAP-tag reagents to label RNAs, although these need to be washed out of the cell because they are fluorescent when unbound (Xu et al ., 2016). All of the aptamers described here require supplementation with an exogenous fluorophore.…”
Section: Tagging Of Nucleic Acidsmentioning
confidence: 99%
“…A different approach to producing a light-up aptamer is to bind and sequester a contact quencher covalently fused to a fluorophore, enabling easy switching of spectral properties by switching the fluorophore (Arora et al ., 2015). Finally, there is an aptamer that binds benzylguanine derivatives, enabling the use of SNAP-tag reagents to label RNAs, although these need to be washed out of the cell because they are fluorescent when unbound (Xu et al ., 2016). All of the aptamers described here require supplementation with an exogenous fluorophore.…”
Section: Tagging Of Nucleic Acidsmentioning
confidence: 99%
“…To further establish the proof-of-principle, the authors demonstrated that more complex structures provided more active RNAs (by examples of GTP-binding aptamers and ligase ribozymes) [ 112 ]. Notably, the hairpin motif derived in [ 58 ] was then successfully employed by other researchers to generate aptamers for different small-molecule targets [ 113 , 114 ].…”
Section: The Design Of Initial Na Libraries For More Affine Aptamementioning
confidence: 99%
“…Finally, Xu et al developed an RNA aptamer that binds benzylguanine [ 23 ]. While benzylguanine is not a biologically-relevant DNA adduct, it is frequently used in place of O 6 -methylguanine for studies [ 37 ].…”
Section: Aptamers For Damaged Dnamentioning
confidence: 99%